2022
DOI: 10.1590/1518-8345.5815.3613
|View full text |Cite
|
Sign up to set email alerts
|

Intenção em deixar a Enfermagem durante a pandemia de COVID-19

Abstract: Resumo Objetivo: investigar a proporção de profissionais com intenção em deixar a Enfermagem durante a pandemia de COVID-19, bem como os fatores associados a esse desfecho. Método: estudo transversal realizado por meio da aplicação de questionários a 890 profissionais de Enfermagem do município de Pelotas (RS). O desfecho foi identificado por meio do autorrelato obtido a partir de questão própria. Riscos Relativos, bem como seus Intervalos de Confiança (95%), foram calculados para as variáveis independentes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This number of deaths worldwide and an overload of work among nursing professionals, who in various countries suffer from a shortage of personnel and dissatisfaction in their jobs, can influence the abandonment of their profession, affecting the service provided to the population. A recent study in Brazil found that 29.1% of nurses, 22.9% of nursing technicians, and 15.7% of nursing assistants intended to leave their professions due to a lack of institutional support, a high workload, and skin injuries from the use of personal protective equipment [ 16 ]. This scenario must be quantified in each hospital, and each reality is always necessary to establish a link between BS and epidemiological outbreaks and adverse events among nursing professionals in order to establish better work support guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This number of deaths worldwide and an overload of work among nursing professionals, who in various countries suffer from a shortage of personnel and dissatisfaction in their jobs, can influence the abandonment of their profession, affecting the service provided to the population. A recent study in Brazil found that 29.1% of nurses, 22.9% of nursing technicians, and 15.7% of nursing assistants intended to leave their professions due to a lack of institutional support, a high workload, and skin injuries from the use of personal protective equipment [ 16 ]. This scenario must be quantified in each hospital, and each reality is always necessary to establish a link between BS and epidemiological outbreaks and adverse events among nursing professionals in order to establish better work support guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some factors could exacerbate the development of complications derived from work overload and BS; these could be linked to the age group of frontline nursing professionals, the time they work in quarantine areas or are specialized in COVID-19, fewer resources available in health centers, and less specialized training against COVID-19 [ 7 ]. The COVID-19 pandemic has meant an overload of work for nursing professionals and may lead them to have the intention of leaving their profession, which harms the health system and patient care [ 16 ]. SB could be the trigger for this situation, which until now has not been well described in Latin America [ 6 , 7 ], especially in Peru, a country that has been hit hard by the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys have been conducted to determine the impact of the pandemic on nurses' well-being and to identify specific stressors associated with intent to leave. [28][29][30][31][32][33] In the second year of an annual COVID-19 survey conducted by the American Nurses Foundation in 2022, over 12,000 nurses were surveyed to gain additional insight on the effect of the pandemic on nurses, staffing, and intent to leave the profession. Findings included a statistically significant relationship between age and emotional health of nurses; an increase in the percentage of nurses intending to leave their position; and increases in staff shortages, incivility, and bullying.…”
mentioning
confidence: 99%
“…verificou-se que indivíduos que moram sozinhos, são mais ricos e testaram positivo para na prevenção e promoção de saúde. Estes profissionais apresentaram maior prevalência de ideação suicida11,13,15 . A exposição a situações críticas aumenta o risco de sofrimento por conta do impacto psicológico ao lidar com uma série de condições desfavoráveis, com consequências que podem se estender do sofrimento psicológico aos sintomas de saúde mental, como estresse pós traumático, sintomas depressivos, sintomas de ansiedade grave, sintomas psiquiátricos gerais e altos níveis de estresse relacionado ao trabalho21 .No ambiente universitário, professores e alunos também apresentaram alto índice de ideação suicida, por conta do distanciamento social e implantação do ensino remoto12,17 .…”
unclassified